The Saints in Old Norse and Early Modern Icelandic Poetry - Wolf, Kirsten, 1959-; Van Deusen, Natalie M., 1983- (Book collections on Project MUSE., 2017)
"The Saints in Old Norse and Early Modern Icelandic Poetry is a complimentary volume to The Legends of the Saints in Old Norse-Icelandic Prose (UTP 2013). While its predecessor dealt primarily with medieval prose texts about the saints, this volume not only focuses on medieval poems about saints but also on Icelandic devotional poetry created during the early modern period. The handlist organizes saints' names, manuscripts, and editions of individual poems with references to approximate dates of the manuscripts, as well as modern Icelandic editions and translations. Each entry concludes with secondary literature about the poem in question. These features combine to make The Saints in Old Norse and Early Modern Icelandic Poetry an invaluable resource for scholars and students in the field."--